Interrater Reliability Across 7 Established Risk Stratification Protocols in Cardiac Rehabilitation - Ramos Haddad Garcia, Maria Isabela [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Vanzella, Lais Manata [UNESP]; França da Silva, Anne Kastellianne [UNESP]; Takahashi, Carolina [UNESP]; Ribeiro, Felipe [UNESP]; Fernanda da Silva, Paula [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP] (Elsevier, 2021)
Objective: To analyze the interrater agreement among physiotherapists in using 7 risk stratification (RS) protocols to evaluate participants of cardiac rehabilitation (CR) and the main factors associated with disagreements that emerged during the RS process. Design: Cross-sectional observational study. Setting: Outpatient rehabilitation center. Participants: Patients (N=72) enrolled in CR with a diagnosis of cardiovascular disease or cardiovascular risk factors. Mean age was 65.62±12.14 y, and mean body mass index (calculated as weight in kilograms divided by height in meters squared) was 29.18±4.56. Interventions: Not applicable. Main Outcome Measures: The main outcome was to the agreement between 2 physiotherapists in the patients’ RS process, using 7 protocols established in the literature for use in CR: American Association of Cardiovascular and Pulmonary Rehabilitation, American College of Sports Medicine, American Heart Association, Sociedade Brasileira de Cardiologia, Sociedad Española de Cardiología, and Société Française de Cardiologie. In addition, the main disagreement factors were assessed. Results: Interrater agreement was classified as moderate-to-good in the 7 included RS protocols (kappa index between 0.53-0.76). The most important aspects that led to disagreement between physiotherapists were reported in 5 categories. The protocol with the greater agreement index was the American College of Sports Medicine (93.10%; n=67), and the one with the greater disagreement was the American Association of Cardiovascular and Pulmonary Rehabilitation (27.80%; n=20). Conclusions: Moderate-to-good interrater agreement among physiotherapists in using 7 RS protocols was observed. Major disagreements were the definition of abnormal hemodynamic responses, rhythm disorders, left ventricular dysfunction, and interpretation of the patient's clinical characteristics.
Keywords: Cardiac rehabilitation; Cardiovascular diseases; Rehabilitation